Differences in Albizia odoratissima genetic diversity between Hainan Island and mainland populations in China - An, Qi; Feng, Yuanheng; Yang, Zhangqi; Hu, La; Wu, Dongshan; Gong, Guifang (Frontiers in Plant Science, 2024)
Background. This study aimed at exploring unique population genetic characteristics of Albizia odoratissima (Linn. f) Benth on Hainan Island to provide a scientific basis for its rational utilization and protection. Methods. It analyzed the genetic diversity and structure of 280 individuals from 10 subpopulations of A. odoratissima from Hainan Island and Baise City using 16 expression sequence markers -simple sequence repeat markers. Results. The genetic diversity of Hainan population (I = 0.7290, He = 0.4483) was lower than that of the Baise population (I = 0.8722, He = 0.5121). Compared with the Baise population (Nm = 2.0709, FST = 0.1077), the Hainan Island population (Nm = 1.7519, FST = 0.1249) exhibited lower gene flow and higher degree of genetic differentiation. Molecular variance and genetic differentiation analyses showed that the main variation originated from individuals within the subpopulation. There were significant differences in the genetic structure between Hainan and Baise populations. It grouped according to geographical distance, consistent with the Mantel test results (R 2 = 0.77, p = 0.001).In conclusion, the genetic diversity of the island A. odoratissima population was lower than that distributed on land, the two populations exhibited obvious genetic structure differences. Both the degrees of inbreeding and genetic differentiation were higher in the island population than in the land population.